Digital Transformation and Reshaping Corporate Strategies in the Telecommunications Sector: Case Studies (STC -Vodafone) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study explores the impact of digital transformation on reshaping corporate strategies and business models in the telecommunications sector, focusing on STC and Vodafone. The research problem highlights the gap between acquiring technology and formulating a clear strategic vision due to the complexity of digital transformation. The study utilized descriptive-analytical and case study approaches. Findings reveal that digitization is a radical shift significantly enhancing operational and marketing efficiency. It also demonstrates that digital technologies improve financial reporting quality and transparency, bolstering corporate governance. The practices of both companies emphasize that project success relies on human capital, with digital leadership playing a pivotal role in decision-making quality. The study recommends adopting an innovation culture and prioritizing digital transformation in top management training to ensure competitiveness.
Keywords: Digital Transformation; Corporate Strategies; Telecommunications; Operational Efficiency; Digital Leadership; Governance; Business Models